Results from the First-Round of Bangladesh Environmental Technology Verification - Support to Arsenic Mitigation (BETV-SAM) Field Test - Amiri, Ali S; Morsheda, E; Kazi, AI; Siraj, S; Ahmed, S; Akbor, MA (Bangladesh Journal of Scientific and Industrial Research, 2011)
The Bangladesh Environmental Technology Verification - Support to Arsenic Mitigation (BETV-SAM) program objectively assessed thirteen arsenic removal technologies (ARTs) that had been submitted for performance verification, and selected seven technologies for the field testing and performance verification. Each technology was deployed to five hydrogeologically distinct regions of Bangladesh and was tested on five wells (with replicate units installed and tested on two wells). Raw and treated water samples were collected at regular intervals and were analysed for arsenic and other water quality parameters. The data were analysed using standard statistical software and the performance of individual ARTs have been evaluated and compared with the proponent's claim. Two technologies (STAR & CIWP) performed well while five other technologies performed poorly and their claims were rejected. The results of the first-round of the BETV-SAM field testing and performance verification program presented and discussed in this paper, may be important from a technological design and development point of view. Key words: Arsenic removal technology; Field testing; Performance verification; Water quality parameters. DOI: 10.3329/bjsir.v45i4.7325 Bangladesh J. Sci. Ind. Res. 45(4), 289-302, 2010